Workshop “Short Story Writing on Family and Friend Theme” untuk Mengurangi Kecemasan Menulis Berbahasa Asing - Ratri Harida; Rizki Mustikasari; Siti Munifah; Fitriana Kartikasari (Abdimas Universal, 2024)
EFL learners’ anxiety occurs due to lack of experience and confidence in using the language. Writing short stories can be a medium for conveying moral message, or life values ​​to readers. Steps for writing a short story based on the creative writing process in the Jabrohim Workshop/service training related to knowledge and skills regarding writing short stories in English for students at Madiun Recency attended by 23 students. The workshop "Short Story Writing on Family and Friend Theme for Students throughout the Madiun Regency was held at Graha Saraswati STKIP PGRI Ponorogo in three sessions: material presentation, demonstration, and a clinical session on short story creation. Based on the results of the Post-Questionnaire given at the end of the workshop, most participants (84%) stated that this training helped increase their confidence in using English to write about family and friends. This workshop was also considered quite helpful (51%) in reducing anxiety on writing short stories in English. In terms of student performance, 76% of participants rated the performance of the presenters as good, 24% rated it as good, and only 2% said it was not good. 82% of participants also agreed to further training regarding writing short stories in English with different themes.